Redesain Lanskap Tugu 0 Km Indonesia Melalui Pendekatan Perilaku Manusia Pasca Tsunami di Kota Sabang Provinsi Aceh - Ruzeilawati Wasi'atu Lathifah; Dewi Rezalini Anwar (http://arl.faperta.ipb.ac.id/, 2022)
Sabang City is the western boundary of Indonesia and is known as zero kilometer of Indonesia. Zero Km Monument Indonesia is geographical marker and tourist destination in Sabang City. However, landscape of this monument still has problems, such as less up to date monument, dirty and messy surroundings, deck is less secure, there are disturbance of wild monkeys, and lack of existing facilities. Furthermore, as tsunami affected area, local community demonstrated signs of emotional distress and depressive symptoms. This condition can affect human behaviour in utilizing outdoor space and needs to be considered for further development. The objectives of this study include (1) identifying, analyzing, creating synthesis potentials and constraints and (2) creating concept and redesigning landscape of 0 Km Monument Indonesia. The method used in this study is descriptive and spatial analysis method with field observation, questionnaire, interviews, and literature studies. The main concept of this study is to create a tourist destination that can be used as healing spot in Sabang City. This design concept is bungong jeumpa, a natural element that support healing concept and an iconic symbol that represents to Aceh. It is implemented to design pattern, decoration, and plant. The final result of this research is limited to landscape redesign with the final product that consists of site plan, planting plan, section, and 3D impression.